2010
DOI: 10.1167/iovs.09-3983
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 Shifts Macrophage Polarization, Promoting Resistance againstPseudomonas aeruginosaKeratitis

Abstract: These data provide evidence that IL-33 promotes a Th2-type immune response and reduces inflammation by polarizing the Mvarphi production of anti-inflammatory mediators in the cornea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 38 publications
(49 reference statements)
3
66
1
Order By: Relevance
“…In Pneumocystis murina lung infection, IL-33 enhances the killing activity of macrophages (33). An IL-33-mediated reduction of Pseudomonas aeruginosa-induced corneal keratitis correlates with M2 macrophage polarization and the decrease in bacterial numbers in the cornea (34). In our model, IL-33-sensitized peritoneal macrophages displayed a significantly lower phagocytic activity against C. albicans (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…In Pneumocystis murina lung infection, IL-33 enhances the killing activity of macrophages (33). An IL-33-mediated reduction of Pseudomonas aeruginosa-induced corneal keratitis correlates with M2 macrophage polarization and the decrease in bacterial numbers in the cornea (34). In our model, IL-33-sensitized peritoneal macrophages displayed a significantly lower phagocytic activity against C. albicans (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…IL-33 and ST2 are both expressed in the normal cornea in resistant BALB/c mice and susceptible C57BL/6 mice. In a model of corneal infection, the IL-33/ST2 expression levels were significantly higher in infected BALB/c mice than in C57BL/6 mice and decreased after 5 days (17,53). In BALB/c mice, the use of a blocking fusion protein, ST2-Fc, led to impaired control of the bacterial load, improved neutrophil influx, increased levels of proinflammatory and Th1 cytokines in the cornea, and decreased levels of Th2 cytokines (53).…”
Section: The Il-33/st2 Axis and Bacterial Infectionsmentioning
confidence: 98%
“…IL-33 is mainly associated with the initiation or progression of specific Th2 responses through secretion of IL-5 and IL-13. IL-33 contributes to macrophage alternative polarization, dendritic cell regulation, and direct effects on T cells (1,(17)(18)(19)(20). These pleiotropic effects explain how IL-33 plays contrasting roles in human diseases.…”
mentioning
confidence: 99%
“…IL-33 acts on a variety of cells of the innate arm of immunity, including neutrophils, macrophages, dendritic cells, mast cells, basophils, and eosinophils, and functions as an amplifier of inflammation (5)(6)(7)(8)(9)(10)(11)(12)(13). Recent studies have suggested that IL-33 plays a role in infection-related inflammation, as IL-33 is protective against infection by opportunistic pathogens such as Pseudomonas aeruginosa, Pneumocystis murina, Cryptococcus neoformans, and polymicrobes (6,8,9,14). Prior to this study, there had been no publications regarding the role of IL-33 in Candida albicans infections.…”
mentioning
confidence: 99%